INTERNATIONAL AND DOMESTIC LAW ASPECTS OF CROSS-BORDER INSOLVENCY IN ORDER TO ESTABLISHING CROSS-BORDER INSOLVENCY REGULATION IN ASEAN: INDONESIAN PERSPECTIVE - Imanullah, Moch Najib; Latifah, Emmy; Ratri, Pramesthi Dinar Kirana (Indonesia Law Review, 2018)
The increases in cross-border trade has resulted in more companies with assets, business, and presence in multiple jurisdiction. When any of these companies face debt restructuring or insolvency, it confronts a myriad of complex issues in coordinating rescue proposals or winding up the businesses across jurisdictions. Prior to the 1997 economic crisis, insolvency laws in most state economies were generally out of date and irrelevant to the modern commercial needs, particulary the cross-border insolvency matters that has not been well regulated. ASEAN has initiated an integrated economy regional by launching an ASEAN Economic Community on late 2015. It aimed to establish a deeply integrated and highly cohesive ASEAN economy that would support sustained high economic growth and resilience in the face of global economic shocks and volatilities within ASEAN members. Unfortunately, ASEAN member has not prepared a regulation regarding cross-border insolvency matters which could restrains its aim to establish a fully integrated economy regional. Each state members has its own national insolvency laws and proceedings, but none have the schemes that could surpassed the national borders and simplified the procedures. The aspects of cross-border insolvency from both the international law and domestic law of Indonesia is already prepared to deal with foreign proceedings. Both could be adjusted to establish a cross-border regulation in ASEAN. Hence, there should be an in-depth harmonization of cross-border insolvency should be another priority upon ASEAN Economic Community to achieve a fully-integrated economy in ASEAN.